An adsorbent for high-efficiency separation of fluorine-containing gas by utilizing defect sites of beta molecular sieve, a preparation method and application thereof

CN122940183APending Publication Date: 2026-10-20ZHEJIANG UNIV OF TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202611427098.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-15
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0008]虽然已有研究关注Beta分子筛多形体比例的调控,但缺乏通过合成阶段原位调控多晶形体 A/B比例至特定范围来系统优化孔道连通性和缺陷位暴露程度的策略,尤其是将调控目标与含氟气体吸附分离性能建立关联

Benefits of technology

(1)本发明中的Beta分子筛的缺陷位调控方法,通过调节水热合成条件控制Beta分子筛中多晶形体A与多晶形体B的相对比例,实现对制备的产品孔道连通性和晶格缺陷的调控,无需后处理引入外来物种,实现Beta分子筛孔道尺寸的精确剪裁和阳离子活性吸附位的有效接触。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

This invention discloses an adsorbent for efficient separation of fluorine-containing gases by utilizing the defect site regulation of Beta molecular sieves, its preparation method, and its applications. The Beta molecular sieve possesses a BEA topology. Through the regulation of the polymorphic coexistence ratio and charge-balanced cation-induced lattice contraction, the defect site structure is weakened, resulting in a molecular sieve adsorbent with regular channels and fully exposed active sites. Contacting the regularly pore-structured Beta molecular sieve with a C2ClF5 / C2F6 fluorine-containing gas mixture allows for selective adsorption of polar C2ClF5 impurities using the exposed cation active sites within the channels. The dynamic separation selectivity of C2ClF5 / C2F6 can reach 5.0–15.0. This invention, through precise regulation of the lattice defects of the Beta molecular sieve, significantly improves the molecular sieve's ability to identify structurally similar fluorine-containing gases and its mass transfer efficiency, providing a feasible path for the efficient purification of fluorine-containing electronic specialty gases.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of gas phase adsorption and separation technology, specifically relating to an adsorbent that utilizes the defect site regulation of Beta molecular sieve to achieve efficient separation of fluorine-containing gases, its preparation method, and its application. Background Technology

[0002] Fluorine-containing gases, especially hexafluoroethane (C₂F₆), are key process gases for dry etching and cavity cleaning in integrated circuits, and their purity directly affects the precision and yield of chip manufacturing. Industrially, C₂F₆ is usually produced from pentafluorochloroethane (C₂ClF₅) via a fluorination reaction, but trace amounts of C₂ClF₅ impurities inevitably remain in the product. Because the boiling points (C₂F₆: 195.1 K, C₂ClF₅: 234.1 K), molecular sizes (kinetic diameters of 0.51 nm and 0.52 nm, respectively), and chemical affinities of the two are extremely similar, traditional cryogenic distillation, membrane separation, and solvent absorption techniques face bottlenecks such as high energy consumption, poor selectivity, or complex processes. Molecular sieve adsorption separation technology, due to its advantages of mild operating conditions, high selectivity, and low energy consumption, shows great potential in the purification of fluorine-containing gases.

[0003] Existing research has found that while activated carbon has a certain adsorption and capture capacity for fluorides such as C2F6, its heterogeneous pore structure and complex surface chemistry limit its selective separation ability. Metal-organic frameworks (MOFs) have also attracted widespread attention in the field of C2F6 adsorption and purification, with some MOFs exhibiting excellent selectivity for the C2F6 / CF4 system. However, MOFs generally suffer from poor hydrothermal stability, high preparation costs, and difficulties in large-scale production, limiting their practical application in industrial gas separation scenarios. Another study compared the adsorption performance of three zeolites—Y-type, ZSM-5, and Beta—for octafluoropropane (C3F8) and octafluorocyclobutane (C4F8) at room temperature, finding that Beta zeolite had a longer breakthrough time for fluorine-containing gases (Chemosphere, 2024, 368: 143706). Other studies have shown that 3A, 4A, and 5A molecular sieves hardly adsorb perfluorocarbon gases such as CF4 and C2F6. The main reason is that the kinetic size of these nonpolar molecules does not match the pore size of the molecular sieve and there is a strong electrostatic repulsion (Journal of Electrical Engineering, 2020, 35(Supplement 2): 499-508). In terms of the C2ClF5 / C2F6 separation system, Zhang Jinke et al. accurately measured the adsorption isotherms of C2ClF5 and C2F6 on NaX molecular sieves and found that the interaction force between NaX and C2ClF5 is significantly greater than that between C2F6, which is the fundamental reason why it can separate C2ClF5 / C2F6 (Journal of Advanced Chemical Engineering, 2020, 34(02): 311-317). However, the adsorption selectivity of NaX molecular sieves mainly depends on the electrostatic field of the cations outside the framework. The distribution of active sites is relatively random and difficult to achieve precise control. At the same time, there are patent reports on controlling the Na in the supercage of FAU molecular sieves through organic template agents. + The method for adsorbing and separating C2ClF5 / C2F6 by exchanging site ratio (CN116514138A) is used, but the target of regulation is the cation distribution rather than the intrinsic framework structure of the molecular sieve.

[0004] Currently, researchers have explored various porous adsorption materials for the adsorption and purification of C2F6. One patent discloses a method for preparing ultra-high purity hexafluoroethane using adsorption, employing an adsorbent selected from one, two, or more combinations of molecular sieves (3A, 4A, 5A, NaX, CaX) and activated carbon to remove impurities from crude hexafluoroethane. The resulting hexafluoroethane can achieve a purity of 99.999% or even 99.9999% or higher (CN103910599A). Another patent discloses an adsorbent modified by ion exchange, ball milling, or impregnation methods. This adsorbent is selected from type A molecular sieves, type X molecular sieves, type Y molecular sieves, SiO2, Al2O3, or activated carbon, and can be used to remove organic impurities from crude hexafluoroethane to obtain ultra-high purity hexafluoroethane products with a purity ≥99.999% (CN105327676A). However, the two patents mentioned above mainly focus on the selection of adsorbent types and the optimization of modification methods. They lack a systematic study on the structure-activity relationship between the intrinsic structure of the adsorbent (such as pore topology, crystal ratio, defect site distribution, etc.) and the separation selectivity of C2ClF5 / C2F6. In addition, both patents only report the purity index of the final product (≥99.999% or even 99.9999%), but do not disclose key adsorption performance parameters such as the adsorption capacity, separation selectivity, breakthrough time or yield of the adsorbent for specific impurities.

[0005] The adsorption capacity of molecular sieves for fluorine-containing gases is closely related to their topology and pore size. Among them, Beta molecular sieves have attracted widespread attention in the field of gas adsorption and separation due to their three-dimensional twelve-membered ring cross-channel structure and tunable surface chemistry. Structural analysis has shown that the structure of Beta molecular sieves is essentially a crystal composed of polymorph A and polymorph B stacked along the

[001] direction, and the ratio of the two polymorphs affects the pore connectivity and tortuosity. Existing techniques have reported synthetic strategies for enriching polymorph A, such as using TEAOH in a fluoride medium to obtain Beta molecular sieves with a polymorph A ratio of about 65-70%, and even single-crystal hierarchical porous Beta molecular sieves with a polymorph A ratio of over 90% (CN116495749A). However, these studies mainly focus on the catalytic applications of Beta molecular sieves and have not yet established a correlation between the control of the crystal form ratio and the adsorption and separation performance of fluorine-containing gases.

[0006] Conventionally synthesized Beta molecular sieves have inherent defects. The near-random coexistence of two polymorphs makes it difficult to precisely control the pore connectivity and the distribution of active sites. The adsorption active sites of conventional Beta molecular sieves mainly originate from the equilibrium cations in the pores. However, the proportion of silanol defect sites in the pores can also change due to the influence of synthesis conditions, thereby affecting the accessibility of the cation active sites and the ability to recognize fluorine-containing gas molecules.

[0007] To address the regulation of defect sites in molecular sieves, Chinese patent CN113683099B discloses a method for synthesizing molecular sieves rich in hydroxyl-rich nest defects. By introducing alkylsiloxanes as mixed silicon sources during the synthesis process, and then calcining them to form single-T site framework defects to construct hydroxyl nests, the degree of defects can be controlled relatively precisely. However, this method mainly focuses on the construction of hydroxyl-rich nest defects and does not involve the directional regulation of lattice defects in Beta molecular sieves. Another literature reports the use of NH4F / NH3·H2O solution to fluorinate Beta molecular sieves, thereby improving catalytic activity by removing non-framework aluminum, adjusting the silicon-aluminum ratio and acid properties. However, this method is a post-treatment modification, and the introduction of foreign fluorine species may change the intrinsic surface properties of the molecular sieve. Furthermore, it mainly targets catalytic performance rather than adsorption and separation applications (Petroleum Refining and Chemical Engineering, 2021(12)).

[0008] While existing research has focused on regulating the polymorph ratio of Beta zeolites, there is a lack of strategies to systematically optimize pore connectivity and defect site exposure by in-situ controlling the A / B ratio of polymorphs to a specific range during synthesis, particularly by establishing a correlation between the regulation target and the adsorption and separation performance of fluorine-containing gases. Furthermore, current defect site regulation methods often rely on post-processing to introduce foreign species or organosilicon sources to construct specific defect types, which may introduce uncontrollable changes in the chemical environment or deviate from intrinsic structural characteristics. There are no reports of combining the regulation of the polymorph ratio of Beta zeolites with the highly selective adsorption and separation of the C2ClF5 / C2F6 system.

[0009] This invention achieves the directional weakening of lattice defects in Beta molecular sieves through in-situ regulation of hydrothermal synthesis conditions. Simultaneously, it precisely controls the A / B polymorph ratio while ensuring the system is free of polymorph C. Combined with alkali metal cation exchange, it achieves precise tailoring of the Beta molecular sieve pore size and optimal combination of cation active adsorption sites. This invention is the first to link crystal form ratio regulation with highly selective adsorption and separation of C2ClF5 / C2F6, improving the production efficiency of 99.9999% high-purity C2F6 products. Summary of the Invention

[0010] To address the aforementioned technical problems in the prior art, the present invention aims to provide an adsorbent for efficient separation of fluorine-containing gases by utilizing the defect site regulation of Beta molecular sieves, along with its preparation method and applications. The present invention achieves highly selective adsorption and separation of C2ClF5 / C2F6 mixed gases by controlling the polymorphic coexistence ratio of Beta molecular sieves and optimizing the pore structure and active site distribution.

[0011] The technical solution adopted in this invention is as follows: An adsorbent for efficient separation of fluorine-containing gases by utilizing defect site modulation of Beta molecular sieves is disclosed. The adsorbent is a Beta molecular sieve, the framework of which is composed of a three-dimensional twelve-membered ring intersecting pore system. X-ray diffraction analysis shows characteristic peaks within at least four interplanar spacings *d*: first interplanar spacing *d* = 11.7 ± 0.2 Å, second interplanar spacing *d* = 4.17 ± 0.2 Å, third interplanar spacing *d* = 3.98 ± 0.2 Å, and fourth interplanar spacing *d* = 3.48 ± 0.2 Å. The pore size is 0.50-0.55 nm. The molar ratio of SiO2 / Al2O3 in the chemical composition of the Beta molecular sieve is 10-30, preferably within the range of 10-15. 29 Si MAS NMR spectrum calculations yielded silanol nest defects (Q) in Beta molecular sieves. 3 The species, namely Si(OSi)3(OH)), accounts for 4-8%, preferably 4.5-5.7%.

[0012] Furthermore, the Beta molecular sieve contains polymorphs A and B, and does not contain polymorph C. The relative proportion of polymorph A is 25-35%, preferably 26%-33%.

[0013] Furthermore, the method for preparing the adsorbent includes the following steps: S1: Dissolve aluminum source, alkali metal source, and organic template agent in deionized water and stir to react. Then add silicon source dropwise to the mixed solution and continue stirring to obtain initial gel. Transfer the initial gel to a pressure-resistant container and seal it. Perform hydrothermal reaction at 400~450K for 20~96h. S2: After the reaction in step S1 is completed, filter, wash, and dry the product, and then calcine it at 800-850 K for 4-8 h. S3: Immerse the product after calcination in step S2 in a 0.1-1M sodium nitrate or potassium nitrate aqueous solution and stir at room temperature to carry out ion exchange. After each ion exchange, centrifuge and wash the sample. Repeat the above ion exchange and washing process 2-5 times. Finally, dry the obtained solid to obtain the adsorbent product.

[0014] Further, in step S1, the aluminum source is one or more of sodium aluminate, aluminum oxide, aluminum hydroxide, aluminum isopropoxide, and aluminum sec-butoxide; the silicon source is one or more of activated silica sol, tetraethyl orthosilicate, and sodium silicate.

[0015] Further, in step S1, the molar ratio of silicon source (in the form of SiO2) to aluminum source (in the form of Al2O3) in the initial gel is 5~30:1, preferably 10~15:1.

[0016] Further, in step S1, the organic template agent is TEAOH, and the molar ratio of the organic template agent to the aluminum source in the initial gel, in the form of Al2O3, is 1.5~11:1, preferably 1.7~3.2:1.

[0017] Further, in step S1, the alkali metal source in the initial gel is NaOH or KOH, and the molar amount of the alkali metal source is 5-25% of the total molar amount of the silicon source in the form of SiO2 and the aluminum source in the form of Al2O3, preferably 18-20%.

[0018] Furthermore, in step S1, the temperature of the hydrothermal reaction is 440-450K, and the reaction time is 20-25h.

[0019] Further, in step S3, the concentration of the sodium nitrate or potassium nitrate aqueous solution is 0.4-0.5M, and the solid-liquid mass-volume ratio of the product after calcination in step S2 to the sodium nitrate or potassium nitrate aqueous solution is 1g:100-150mL.

[0020] The present invention also discloses the application of the adsorbent in the separation and purification of fluorine-containing gases, wherein the fluorine-containing gas is a mixture of C2ClF5 and C2F6, wherein the concentration of C2ClF5 is 10%~50%; the adsorbent selectively adsorbs C2ClF5 using the cationic active sites exposed in the molecular sieve channels, thereby purifying C2F6.

[0021] Furthermore, the adsorption operation is carried out in a fixed-bed adsorption device at ambient temperature and pressure, and the purity of the separated C2F6 product is not less than 99.9999%.

[0022] In the adsorption application of the Beta molecular sieve, when the concentration of C2ClF5 in the feed is 10%, the single-pass yield of C2F6 by the Beta molecular sieve is 100~118 L / kg; when the concentration of C2ClF5 in the feed is 50%, the single-pass yield of C2F6 is 16~31 L / kg.

[0023] Compared with the prior art, the beneficial effects achieved by the present invention are: (1) The defect site control method of Beta molecular sieve in this invention controls the relative ratio of polymorph A and polymorph B in Beta molecular sieve by adjusting the hydrothermal synthesis conditions, thereby controlling the pore connectivity and lattice defects of the prepared product. No post-processing is required to introduce foreign species, thus achieving precise tailoring of the pore size of Beta molecular sieve and effective contact of cationic active adsorption sites.

[0024] (2) The present invention uses a single Beta molecular sieve adsorbent, which can achieve a separation effect of C2F6 purity not less than 99.9999% (6N) at room temperature and pressure. The separation selectivity can reach up to 15.0, and the single-pass yield can reach up to 118 L / kg, which is better than conventional commercial molecular sieves (such as NaY-2.6).

[0025] (3) This invention employs a conventional hydrothermal synthesis method, with widely available aluminum and silicon sources. The synthesis conditions are mild, and the post-processing involves only conventional ion exchange and drying. The entire process is simple to operate, requires no special equipment, and has good prospects for industrial application.

[0026] (4) In this invention, low-defect Beta molecular sieves can be directly prepared, and their defect status can be adjusted. Attached Figure Description

[0027] Figure 1 These are the XRD patterns of Na-Beta-1, Na-Beta-2, Na-Beta-3, and Na-Beta-4 zeolites; Figure 2 The XRD patterns are of Na-Beta-5, K-Beta-5 and K-Beta-12.5 zeolites; Figure 3 These are high-resolution transmission electron microscopy images and fast Fourier transform images of Na-Beta-1 zeolite. Figure 4 These are high-resolution transmission electron microscopy images and fast Fourier transform images of Na-Beta-2 zeolite. Figure 5 These are high-resolution transmission electron microscopy images and fast Fourier transform images of Na-Beta-3 zeolite. Figure 6 These are high-resolution transmission electron microscopy images and fast Fourier transform images of Na-Beta-4 zeolite. Figure 7 These are high-resolution transmission electron microscopy images and fast Fourier transform images of Na-Beta-5 zeolite. Figure 8 These are high-resolution transmission electron microscopy (TEM) images and fast Fourier transform (FFT) images of K-Beta-5 zeolite; Figure 9These are high-resolution transmission electron microscopy (TEM) images and fast Fourier transform (FFT) images of Na-Beta-12.5 zeolite. Figure 10 The adsorption and separation curves of Na-Beta-1 for the C2ClF5 / C2F6 (volume ratio 5 / 5) system are shown. Figure 11 The adsorption separation curve of Na-Beta-2 for the C2ClF5 / C2F6 (volume ratio 5 / 5) system is shown. Figure 12 The adsorption separation curve of Na-Beta-3 for the C2ClF5 / C2F6 (volume ratio 5 / 5) system is shown. Figure 13 The adsorption and separation curves of Na-Beta-4 for the C2ClF5 / C2F6 (volume ratio 5 / 5) system are shown. Figure 14 The adsorption and separation curves of Na-Beta-5 for the C2ClF5 / C2F6 (volume ratio 5 / 5) system are shown. Figure 15 The adsorption separation curve of K-Beta-5 for the C2ClF5 / C2F6 (volume ratio 5 / 5) system is shown. Figure 16 The adsorption separation curve of K-Beta-12.5 for the C2ClF5 / C2F6 (volume ratio 5 / 5) system is shown. Figure 17 The adsorption separation curve of Na-ALFA-Beta for the C2ClF5 / C2F6 (volume ratio 5 / 5) system is shown. Figure 18 The adsorption and separation curves of Na-Beta-5 for the C2ClF5 / C2F6 (volume ratio 1 / 9) system are shown. Figure 19 The adsorption and separation curves of K-Beta-5 for the C2ClF5 / C2F6 (volume ratio 1 / 9) system are shown. Figure 20 The adsorption separation curve of K-Beta-12.5 for the C2ClF5 / C2F6 (volume ratio 1 / 9) system is shown. Figure 21 This is the adsorption and separation curve of NaY for the C2ClF5 / C2F6 (volume ratio 1 / 9) system. Detailed Implementation

[0028] The present invention is described in detail below through embodiments, but the present invention is not limited to these embodiments.

[0029] X-ray diffraction analysis: The X-ray diffraction pattern was recorded using an X'Pert PRO powder diffractometer (equipped with copper Kα radiation, wavelength λ=0.1541 nm). The pattern acquisition range was 2θ from 10° to 90°, with a step size of 0.013°.

[0030] High-resolution transmission electron microscopy (HRTEM) measurements: The instrument used was a FEI Tecnai G2 F30 S-Twin high-resolution transmission electron microscope (HRTEM) with an operating voltage of 300 kV. Samples were pretreated before HRTEM testing. The pretreatment steps were as follows: the sample was ground, ultrasonically dispersed in ethanol, dropped onto a copper grid of a microgrid carbon support film, and dried under an infrared lamp to evaporate the solvent.

[0031] Solid-state nuclear magnetic resonance (SsNMR) spectroscopy: The instrument used was a Bruker AVANCE-III 400 MHz spectrometer. The sample needed to be dehydrated under vacuum before the experiment. Specific operating conditions included a heating rate of 5 K / min to 573 K, and maintaining this temperature below 10 °C. -3 Maintain this temperature for 3 hours under a pressure of Pa.

[0032] R115 / R116 Adsorption Separation Determination: Dynamic adsorption experiments were conducted in a continuous flow fixed-bed reactor at atmospheric pressure. In each test, 2.0 g of zeolite was placed in a U-tube reactor. Prior to the test, the zeolite sample was pretreated for 3 h at 573 K and a N2 flow rate of 100 ml / min to completely remove adsorbed water and impurity gases. After activation, the temperature was switched to the test temperature, and the gas flow rate was switched to a constant total flow rate mixed gas atmosphere (C2ClF5 / C2F6 = 5 / 5 or 1 / 9, volume ratio). The outlet gas concentration was continuously measured by automatic sampling into a gas chromatograph (Agilent 6890) equipped with a thermal conductivity detector (TCD) and a Hayesep Q column until adsorption equilibrium was reached. In actual gas adsorption determination, the C2ClF5 / C2F6 adsorption selectivity was calculated using the following formula: .

[0033] Here, The q represents the adsorption selectivity of C2ClF5 compared to C2F6, and q represents the saturated adsorption capacity (mmol·g) of the molecular sieve for different gases. -1 ), p represents the partial pressure (kPa) of a specific gas in the gas mixture.

[0034] Example 1: An adsorbent for efficient separation of fluorine-containing gases using defect site modulation of Beta molecular sieves and its performance testing: S1: Sodium aluminate, sodium hydroxide, tetraethylammonium hydroxide, and deionized water were mixed and stirred for about 15 minutes according to the molar ratio of 1 Al2O3 (sodium aluminate in Al2O3 form): 30 SiO2 (active silica sol in SiO2 form): 600 H2O: 11 TEAOH: 4 NaOH. Ludox-AS40 was then added dropwise to the mixture to form an aluminosilicate gel. After stirring for about 2 hours, the mixture was transferred to a stainless steel autoclave. The autoclave was sealed and the mixture was subjected to hydrothermal reaction at 443 K for 23 h. After the reaction, the mixture was centrifuged and washed four times, dried overnight at 373 K, and then calcined at 823 K in air for 6 h. After cooling to room temperature, the zeolite precursor was obtained.

[0035] S2: The calcined zeolite precursor from step S1 was mixed with 0.5 mol / L sodium nitrate solution at a solid-liquid mass-volume ratio of 1 g: 150 mL. The mixture was stirred at room temperature for 16 h of ion exchange. After each ion exchange, the sample was centrifuged and washed. The above ion exchange and washing process was repeated three times. Finally, the obtained solid was placed in a 373 K oven overnight to obtain the final zeolite adsorbent product, which was named Na-Beta-1.

[0036] The sample obtained in Example 1 was subjected to XRD testing. The interplanar spacing at the characteristic peaks in Na-Beta-1 is shown in Table 1. A schematic diagram of the XRD test results is shown in [the diagram]. Figure 1 This indicates that the synthesized molecular sieve has a standard Beta molecular sieve configuration. Furthermore, deconvolution analysis within the 2θ = 5°–10° range shows that polymorph A contains 26% and polymorph B contains 74%.

[0037] Table 1 Characteristic interplanar spacings of Na-Beta-1 .

[0038] The Na-Beta-1 sample from Example 1 was preprocessed before testing, characterized by HRTEM, and Fourier transform was performed on the HRTEM images. The HRTEM results are as follows. Figure 3 This shows that Na-Beta-1 has a complete and ordered framework arrangement, with clear and continuous lattice fringes. Simultaneously, using... 29 The coordination of framework atoms was detected by Si MAS NMR spectrum, and the proportion of silanol nest defects in Na-Beta-1 was calculated to be 5.7% based on the spectrum.

[0039] The CO2 adsorption pore size of Na-Beta-1 was analyzed, and the results showed that the pore size distribution of Na-Beta-1 was concentrated in the range of 0.48-0.7 nm.

[0040] The preparation method of the molecular sieve of Comparative Example 1 was repeated in Example 1, except that "in step S1, the hydrothermal reaction treatment temperature was 413K and the reaction time was extended to 4 days". All other operating conditions and steps remained unchanged, and the corresponding zeolite adsorbent product was obtained and named Na-Beta-2.

[0041] The obtained samples were subjected to XRD testing. The interplanar spacing at the characteristic peaks in Na-Beta-2 is shown in Table 2. A schematic diagram of the XRD test results is shown in [the diagram]. Figure 1 This indicates that the synthesized molecular sieve has a standard Beta molecular sieve configuration. Furthermore, deconvolution analysis within the 2θ = 5°–10° range shows that the content of polymorph A increases to 40%, while the content of polymorph B is 60%.

[0042] Table 2 Characteristic interplanar spacings of Na-Beta-2 .

[0043] The obtained product Na-Beta-2 was characterized by HRTEM, and the HRTEM images were subjected to Fourier transform. The results of HRTEM are as follows. Figure 4 This shows that Na-Beta-2 exhibits localized channel distortion, with blurred lattice fringes in some areas. Simultaneously, using... 29 The coordination of framework atoms was detected by Si MAS NMR spectrum, and the proportion of silanol nest defects in Na-Beta-2 was calculated to be 7% based on the spectrum.

[0044] The CO2 adsorption pore size analysis of Na-Beta-2 showed that the pore size distribution of Na-Beta-2 was concentrated in the range of 0.48-0.7 nm, and also concentrated in the range of 0.4-0.5 nm.

[0045] The preparation method of the molecular sieve in Comparative Example 2 was the same as that in Example 1, except that "in step S1, the hydrothermal reaction temperature was 433K and the reaction time was extended to 4 days". All other operating conditions and steps remained unchanged, and the corresponding zeolite adsorbent product was obtained and named Na-Beta-3.

[0046] The obtained samples were subjected to XRD testing. The interplanar spacings at the characteristic peaks in Na-Beta-3 are shown in Table 3. A schematic diagram of the XRD test results is shown in [the diagram]. Figure 1 This indicates that the synthesized molecular sieve has a standard Beta molecular sieve configuration. Furthermore, deconvolution analysis within the 2θ = 5°–10° range shows that polymorph A contains 36% and polymorph B contains 64%.

[0047] Table 3 Characteristic interplanar spacings of Na-Beta-3 .

[0048] The obtained product Na-Beta-3 was characterized by HRTEM, and the HRTEM images were subjected to Fourier transform. The results of HRTEM are as follows. Figure 5 This shows that Na-Beta-3 exhibits localized channel distortion, with blurred lattice fringes in some areas. Simultaneously, using... 29 The coordination of framework atoms was detected by Si MAS NMR spectrum, and the proportion of silanol nest defects in Na-Beta-3 was calculated to be 6.3% based on the spectrum.

[0049] The CO2 adsorption pore size of Na-Beta-3 was analyzed. The results showed that the pore size distribution of Na-Beta-3 was concentrated in the range of 0.48-0.7 nm, and also concentrated in the range of 0.4-0.5 nm.

[0050] Example 2: An adsorbent for efficient separation of fluorine-containing gases using defect site modulation of Beta molecular sieves and its performance testing: S1: Alumina, tetraethylammonium hydroxide, and deionized water were mixed and stirred for about 15 minutes according to a molar ratio of 1:30 for Al2O3:30 for SiO2:245 for tetraethyl orthosilicate:5 for H2O:5 for TEAOH:2 for NaOH. Then, tetraethyl orthosilicate was added to the mixture to prepare an aluminosilicate gel. After stirring continuously for about 2 hours, the gel was transferred to a stainless steel autoclave and hydrothermally treated at 443 K for 23 h. After washing four times, the gel was dried overnight at 398 K and then calcined at 823 K for 6 h to obtain Beta molecular sieves. Cooling to room temperature yielded the zeolite precursor.

[0051] S2: The ion exchange process in step S2 of Example 2 is the same as that in Example 1, and the product obtained is named Na-Beta-4.

[0052] The obtained samples were subjected to XRD testing. The interplanar spacing at the characteristic peaks in Na-Beta-4 is shown in Table 4. A schematic diagram of the XRD test results is shown in [the diagram]. Figure 1 This indicates that the synthesized molecular sieve has a standard Beta molecular sieve configuration. Furthermore, deconvolution analysis within the 2θ = 5°–10° range shows that polymorph A content is up to 45%, and polymorph B content is 55%.

[0053] Table 4 Characteristic interplanar spacings of Na-Beta-3 .

[0054] The obtained product Na-Beta-4 was preprocessed before the experiment, characterized using HRTEM, and Fourier transform was performed on the HRTEM images. The results are as follows. Figure 6 The results showed that Na-Beta-4 had good crystallinity, but some degree of pore distortion existed in local areas, similar to Na-Beta-2 but slightly less severe. Simultaneously, using... 29 The coordination of framework atoms was detected by Si MAS NMR spectrum, and the proportion of silanol nest defects in Na-Beta-4 was calculated to be 8% based on the spectrum.

[0055] CO2 adsorption pore size analysis of Na-Beta-4 showed that the proportion of effective micropores (0.48~0.70 nm) in the pore size distribution of Na-Beta-4 was slightly higher than that of Na-Beta-2, but there were also defect sites that caused the effective pore size of some channels to shrink from 0.56 nm to 0.4~0.5 nm.

[0056] Example 3: An adsorbent for efficient separation of fluorine-containing gases using defect site modulation of Beta molecular sieves and its performance testing: S1: Aluminum hydroxide, tetraethylammonium hydroxide, and deionized water were mixed in a lined container at a molar ratio of 0.5 Al₂O₃ (aluminum hydroxide in Al₂O₃ form): 5 SiO₂ (sodium silicate in SiO₂ form): 27 H₂O: 0.85 TEAOH: 1 NaOH, and the mixture was stirred continuously for approximately 15 minutes. Sodium silicate was then added to the mixture, and stirring continued for approximately 2 hours. The crystallization process was carried out in a stainless steel autoclave lined with polytetrafluoroethylene at 443 K for 23 hours. After the reaction, the resulting solid was filtered, washed with distilled water, dried overnight at 373 K, and finally calcined at 823 K for 6 hours.

[0057] S2: The ion exchange process in step S2 of Example 3 is the same as that in Example 1, and Beta zeolite is obtained and named Na-Beta-5.

[0058] The obtained samples were subjected to XRD testing. The interplanar spacings at the characteristic peaks in Na-Beta-5 are shown in Table 5. A schematic diagram of the XRD test results is shown in [the diagram]. Figure 2 This indicates that the synthesized molecular sieve has a standard Beta molecular sieve configuration. Furthermore, deconvolution analysis within the 2θ = 5°–10° range shows that polymorph A contains 33% and polymorph B contains 67%.

[0059] Table 5 Characteristic interplanar spacings of Na-Beta-5 .

[0060] The obtained product Na-Beta-5 was characterized using HRTEM, and the HRTEM images were subjected to Fourier transform. The results are as follows: Figure 7 This confirmed the presence of significant stacking faults or grain boundary defects within the material, interspersed with a normally ordered arrangement of pores. Simultaneously, using... 29 The coordination of framework atoms was detected by Si MAS NMR spectrum, and the proportion of silanol nest defects in Na-Beta-5 was calculated to be 4.7% based on the spectrum.

[0061] The CO2 adsorption pore size of Na-Beta-5 was analyzed, and the results showed that the pore size distribution of Na-Beta-5 was concentrated in the range of 0.48-0.7 nm.

[0062] Example 4: The preparation method of the molecular sieve in Example 4 is the same as that in Example 3, with the only differences being the following two points: 1) In step S1, the aluminum source is replaced with aluminum sec-butoxide, the silicon source is replaced with Ludox-AS40, and the molar ratio of all raw materials is replaced with 0.5 Al2O3 (the amount of aluminum sec-butoxide is in the form of Al2O3): 5 SiO2 (the amount of active silica sol is in the form of SiO2): 27 H2O: 0.85 TEAOH: 1 KOH.

[0063] 2) In step S2, the 0.5 mol / L sodium nitrate solution was replaced with an equal volume of 0.5 mol / L potassium nitrate solution, while the other conditions remained unchanged. The resulting molecular sieve was named K-Beta-5.

[0064] The obtained samples were subjected to XRD testing. The interplanar spacings at the characteristic peaks in K-Beta-5 are shown in Table 6. A schematic diagram of the XRD test results is shown in [the diagram]. Figure 2 This indicates that the synthesized molecular sieve has a standard Beta molecular sieve configuration. Furthermore, deconvolution analysis within the 2θ = 5°–10° range shows that polymorph A contains 29% and polymorph B contains 71%.

[0065] Table 6 Characteristic interplanar spacings of K-Beta-5 .

[0066] The obtained product K-Beta-5 was characterized using HRTEM, and the HRTEM image was subjected to Fourier transform. The results are as follows. Figure 8 This confirmed that K-Beta-5 exhibits a clear, continuous, and long-range ordered pore arrangement, indicating that the sample has extremely high crystallinity and a complete framework structure. Simultaneously, using... 29The coordination of framework atoms was detected by Si MAS NMR spectrum, and the proportion of silanol nest defects in K-Beta-5 was calculated to be 4.5% based on the spectrum.

[0067] CO2 adsorption pore size analysis of K-Beta-5 showed that the pore size distribution of K-Beta-5 is a single symmetrical peak, which allows its pore size to be precisely tuned to 0.5008 nm, a precise match with the molecular size of C2ClF5.

[0068] The preparation method of the molecular sieves in Comparative Example 3 was repeated in Example 4, except that in step S1, the molar ratio of all raw materials was replaced with 1 Al2O3 (aluminum sec-butoxide in Al2O3 form): 25 SiO2 (active silica sol in SiO2 form): 27 H2O: 0.85 TEAOH: 1 KOH. All other operating conditions and steps remained unchanged, resulting in the corresponding zeolite adsorbent product, named K-Beta-12.5.

[0069] The obtained samples were subjected to XRD testing. The interplanar spacing at the characteristic peaks in K-Beta-12.5 is shown in Table 7. A schematic diagram of the XRD test results is shown in [the diagram]. Figure 2 This indicates that the synthesized molecular sieve has a standard Beta molecular sieve configuration. Furthermore, deconvolution analysis within the 2θ = 5°–10° range shows that polymorph A contains 34% and polymorph B contains 66%.

[0070] Table 7 Characteristic interplanar spacings of K-Beta-12.5 .

[0071] The obtained product K-Beta-12.5 was characterized using HRTEM, and Fourier transform was performed on the HRTEM images. The results are as follows: Figure 9 This confirmed that K-Beta-12.5 exhibits localized channel distortion, with blurred lattice fringes in some areas, indicating a certain degree of channel distortion in local regions of the sample. Simultaneously, using... 29 The coordination of framework atoms was detected by Si MAS NMR spectrum, and the proportion of silanol nest defects in K-Beta-12.5 was calculated to be 5.2% based on the spectrum.

[0072] The CO2 adsorption pore size of K-Beta-12.5 was analyzed. The results showed that the pore size distribution of K-Beta-12.5 was a single symmetrical peak, with the pore size concentrated in the range of 0.45-0.54 nm and 0.57-0.63 nm.

[0073] Application Example 1: Adsorption Performance Test Experiment of Different Molecular Sieves Commercial Na-ALFA-Beta molecular sieves with a silica-to-alumina ratio of 40, purchased from Alfa Esa, were used, along with molecular sieve samples from Examples 1, 1, 2, 2, 3, 4, and 3. Each molecular sieve sample weighed 2.0 g and was placed in a U-tube reactor. Before testing, the zeolite samples were pretreated at 573 K and 100 ml / min N₂ flow rate for 3 h to completely remove adsorbed water and impurity gases. Then, a C₂ClF₅ / C₂F₆ mixed gas with a C₂ClF₅ concentration of 50% was introduced for adsorption separation testing. The adsorption separation curves for different molecular sieves are shown below. Figures 10-17 The adsorption results of different zeolite adsorbents obtained by calculation are shown in Table 8.

[0074] Table 8. Adsorption capacity, adsorption-separation selectivity, and 6N yield of different zeolite molecular sieves for 50% C2ClF5 gas. .

[0075] Application Example 2: Adsorption Performance Test Experiment of Different Molecular Sieves Commercial NaY-2.6 molecular sieves with a silica-to-alumina ratio of 2.6, purchased from Nankai University, were used along with molecular sieve samples from Examples 3, 4, and Comparative Example 3. Each molecular sieve sample weighed 2.0 g and was placed in a U-tube reactor. Before testing, the zeolite samples were pretreated at 573 K and 100 ml / min N2 flow rate for 3 h to completely remove adsorbed water and impurity gases. Then, a C2ClF5 / C2F6 mixed gas system with a C2ClF5 concentration of 10% was introduced for adsorption separation testing. The adsorption separation curves for different molecular sieves are shown below. Figures 18-21 The adsorption and separation results of different zeolite adsorbents are shown in Table 9.

[0076] Table 9. Adsorption capacity, adsorption-separation selectivity, and 6N yield of different zeolite molecular sieves for 10% C2ClF5 gas. .

[0077] A comparison of Na-Beta-1, Na-Beta-2, and Na-Beta-3 reveals that hydrothermal temperature can control the crystal structure ratio of Beta zeolites. Ensuring a sufficiently high crystallization temperature (≥440 K) is prioritized to suppress the formation of co-existing defects, thereby controlling the polymorphic A ratio within a suitable range. Na-Beta-1, with its suitable temperature-controlled polymorphic A ratio at 443 K, achieved the optimal combination of "low defects + regular channels," resulting in the highest 6N yield among all Na-type samples. Furthermore, compared to K-Beta-12.5, the superior performance of K-Beta-5 demonstrates that by controlling the gel silica-alumina ratio (Si / Al≈5), the defect density can be significantly reduced without significantly increasing the A ratio. In contrast, while Na-Beta-1 (A=26%) has lower defects, its silica-alumina ratio limits the total number of active sites. Therefore, the optimal strategy is to maintain the proportion of crystalline form A within the range of 26%-33%, ensuring that the Beta molecular sieve does not excessively induce symbiotic defects while maintaining the topological connectivity of the pores. Simultaneously, a low silica-to-alumina ratio gel is used to increase the density of Al sites in the framework, providing a suitable environment for Na. + / K + Exchange provides more anchoring points. Combining Application Example 1 and Comparative Example 1, a comparison of Na-Beta-1 and Na-Beta-2 revealed that an increase of only 1.3 percentage points in defects led to a decrease in C2ClF5 adsorption capacity from 2.25 to 1.99 mmol / g, selectivity from 5.0 to 4.2, and a dramatic drop in 6N yield from 30.7 to 16.0 L / kg. This indicates that at higher C2ClF5 concentrations, the amplification effect of defects on yield is extremely significant. However, for Na-Beta-4, although it has a higher proportion of silanol nest defects, its selectivity and adsorption capacity are both higher than Na-Beta-2, suggesting that adjusting the defect proportion within a certain range can improve its adsorption performance.

[0078] Figures 10-21 The vertical axis C / C0 represents the penetration concentration ratio, which measures the ratio of a substance's concentration at a given moment to its initial concentration. Figures 10-21As can be seen from the adsorption curves of C2ClF5 / C2F6, the larger the enclosed area between the two lines, the better the separation effect of the adsorbent material on the two. This corresponds to the specific numerical values ​​of the adsorption capacity of the molecular sieve adsorbent for C2ClF5 and the selectivity of C2ClF5 / C2F6 in the table above. Compared with commercial Na-ALFA-Beta molecular sieves, the regulated Na-Beta-1, Na-Beta-5, and K-Beta-5 all exhibit superior adsorption performance in a 50% C2ClF5 system. Na-Beta-5 and K-Beta-5 also show superior adsorption performance compared to the commercial NaY-2.6 molecular sieve in a 10% C2ClF5 system. This demonstrates that by achieving controllable defect site structure within the Beta molecular sieve, precise matching of pore size with C2ClF5 molecules can be achieved, thereby improving the efficient separation of the C2ClF5 and C2F6 system.

[0079] The contents described in this specification are merely an enumeration of the implementation forms of the inventive concept, and the scope of protection of this invention should not be regarded as limited to the specific forms described in the embodiments.

Claims

1. An adsorbent for efficient separation of fluorine-containing gases by utilizing the defect site modulation of Beta molecular sieves, characterized in that, The adsorbent is a Beta molecular sieve, whose framework consists of a three-dimensional twelve-membered ring cross-channel system. X-ray diffraction analysis shows that it exhibits characteristic peaks within at least four interplanar spacings (d): first interplanar spacing d = 11.7 ± 0.2 Å, second interplanar spacing d = 4.17 ± 0.2 Å, third interplanar spacing d = 3.98 ± 0.2 Å, and fourth interplanar spacing d = 3.48 ± 0.2 Å. The molar ratio of SiO2 to Al2O3 in the chemical composition of the Beta molecular sieve is 10⁻³⁰. Depend on 29 The Si MAS NMR spectrum shows that the proportion of silanol nest defects in Beta molecular sieve is 4-8%. The Beta molecular sieve contains both polymorphs A and B, but no polymorph C. The relative proportion of polymorph A is 25-45%.

2. The adsorbent as described in claim 1, characterized in that, The chemical composition of Beta molecular sieves contains an oxide SiO2 / Al2O3 molar ratio of 10⁻¹⁵; 29 The Si MAS NMR spectrum analysis showed that the proportion of silanol nest defects in the Beta molecular sieve was 4.5-5.7%, and the relative content of polymorph A in the Beta molecular sieve was 26%-35%.

3. The method for preparing the adsorbent as described in claim 1 or 2, characterized in that, Includes the following steps: S1: Dissolve aluminum source, alkali metal source, and organic template agent in deionized water and stir to react. Then add silicon source dropwise to the mixed solution and continue stirring to obtain initial gel. Transfer the initial gel to a pressure-resistant container and seal it. Perform hydrothermal reaction at 400~450K for 20~96h. S2: After the reaction in step S1 is completed, filter, wash, and dry the product, and then calcine it at 800-850 K for 4-8 h. S3: Immerse the product after calcination in step S2 in a 0.1-1M sodium nitrate or potassium nitrate aqueous solution and stir at room temperature to carry out ion exchange. After each ion exchange, centrifuge and wash the sample. Repeat the above ion exchange and washing process 2-5 times. Finally, dry the obtained solid to obtain the adsorbent product.

4. The preparation method according to claim 3, characterized in that, In step S1, the aluminum source is one or more of sodium aluminate, aluminum oxide, aluminum hydroxide, aluminum isopropoxide, and aluminum sec-butoxide; the silicon source is one or more of activated silica sol, tetraethyl orthosilicate, and sodium silicate. The molar ratio of silicon source (in the form of SiO2) to aluminum source (in the form of Al2O3) in the initial gel is 5~30:1; The organic template agent is tetraethylammonium hydroxide (TEAOH), and the molar ratio of the organic template agent to the aluminum source in the initial gel, in the form of Al2O3, is 1.5~11:

1. The alkali metal source in the initial gel is NaOH or KOH, and the molar amount of the alkali metal source is 5-25% of the total molar amount of the silicon source in the form of SiO2 and the aluminum source in the form of Al2O3.

5. The preparation method according to claim 4, characterized in that, The molar ratio of silicon source (in the form of SiO2) to aluminum source (in the form of Al2O3) in the initial gel is 10~15:1; The molar ratio of the organic template agent to the aluminum source in the initial gel, expressed as Al2O3, is 1.7~3.2:1; The molar amount of the alkali metal source is 18-20% of the total molar amount of the silicon source (in SiO2 form) and the aluminum source (in Al2O3 form).

6. The preparation method according to claim 3, characterized in that, In step S1, the hydrothermal reaction temperature is 440-450K and the reaction time is 20-25h.

7. The preparation method according to claim 3, characterized in that, In step S3, the concentration of the sodium nitrate or potassium nitrate aqueous solution is 0.4-0.5M, and the solid-liquid mass-volume ratio of the product after calcination in step S2 to the sodium nitrate or potassium nitrate aqueous solution is 1g:100-150mL.

8. The application of the adsorbent as described in claim 1 or 2 in the separation and purification of fluorine-containing gases.

9. The application as described in claim 8, characterized in that, The fluorine-containing gas is a mixture of C2ClF5 and C2F6, wherein the volume concentration of C2ClF5 is 10%~50%; the adsorbent selectively adsorbs C2ClF5 using the exposed cationic active sites within the molecular sieve channels, thereby purifying C2F6.

10. The application as described in claim 9, characterized in that, The adsorption operation is carried out in a fixed-bed adsorption device at ambient temperature and pressure, and the purity of the separated C2F6 product is not less than 99.9999%.

Citation Information

Patent Citations

  • Ultra-high purity hexafluoroethane preparation method

    CN103910599A

  • Modified adsorbent and application of same in preparation of ultra-pure hexafluoroethane

    CN105327676A

  • A method for synthesizing defective zeolite molecular sieves rich in hydroxyl groups

    CN113683099B

  • Preparation method of single crystal hierarchical pore chiral crystal form A enriched Beta molecular sieve

    CN116495749A

  • High-silicon FAU molecular sieve with high-proportion exposed acid site as well as preparation method and application of high-silicon FAU molecular sieve

    CN116514138A